Fabrication and testing of epoxy resin-based composites for electrical insulation material applications - Prasetyo, Moh Toni; Sulistyo, Sulistyo; Nugroho, Sri; Abdul, Syakur; Amir Izzani, Mohamed (Semarak Ilmu Publishing, 2025)
Electrical insulation materials are a critical component in the design and development of electrical systems, playing a crucial role in ensuring the safe and efficient transmission and distribution of electrical power. The aim of this study is to examine the effect of incorporating rice husk ash and silane on the hydrophobicity, leakage current, and tensile strength properties of composite specimens. This study focused on fabricating composites by varying filler concentrations, using epoxy resin as the matrix. The specimens RTV 10, RTV 20, RTV 30, RTV 40, and RTV 50 utilized a filler composed of rice husk ash and silane, with concentrations of 10%, 20%, 30%, 40%, and 50%, respectively. The obtained samples were subjected to testing for leakage current, tensile strength, and water contact angle (hydrophobicity). The study results indicate that increasing the filler content to 40 wt.% in RTV 40 specimens improves the composite’s tracking time, and hydrophobic properties. RTV 40 specimens demonstrated the longest tracking time and the most favourable hydrophobic characteristics compared to the other specimens. However, when the filler content exceeds 40 wt.%, the water contact angle decreases, leading to higher leakage currents and diminished insulating effectiveness. For the RTV 40 specimen, the measured values were a water contact angle of 92°, a tracking time of 1956 seconds, and a tensile strength of 39.59 N/mm². This study addresses several points of the Sustainable Development Goals (SDGs) by improving material properties (SDG 9), promoting sustainable materials (SDG 12) and improving energy-efficient infrastructure (SDG 7).